Analisis Sistem Informasi Akuntansi Penjualan Tunai Dan Penerimaan Kas Pada Pintar Asia Swalayan Maumere - Veronica Yasintha Sedo Branyor (Student Research Journal, 2023)
This research was conducted at Pintar Asia Supermarkets Maumere. The purpose of this study was to determine the accounting information system for cash sales and cash receipts that has been running at the Pintar Asia Swalayan Maumere company. The type of research used is qualitative research, where data is obtained from interviews with informants and supporting documentation in the form of an overview and organizational structure. The results showed that the accounting information system applied at Pintar Asia Swalayan Maumere in processing sales transactions and cash receipts has been able to produce good information. However, in practice, the company's organizational structure has described the division of tasks and authority for each section, but has not been implemented properly and effectively. This is because there are still dual tasks in the accounting function and cash function which should be held by the finance admin (accounting function), and the cash function which is actually held by the cashier and head of operations. The sales activities of Pintar Asia Swalayan Maumere are also still implementing a cash sales system, and have not yet implemented an online or digital transaction system.